2022
DOI: 10.1007/s10551-022-05314-8
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Culture of Solidarity Through a Three-Step Virtuous Process: Lessons from Common Good-Oriented Organizations

Abstract: Solidarity is a principle oriented toward the common good that ensures that each person can have the necessary goods and services for a dignified life. As such, it is very often approached in a theoretical manner. In this empirical study, we explored the development of a culture of solidarity within an organizational context. In particular, we qualitatively investigated how a culture of solidarity can concretely spread within and beyond organizations by conducting 68 semi-structured interviews with members of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…This helps conceive solidarity as a common good as we seek the well-being according to the needs of others. For this reason, Frémeaux et al (2023) present six subgroups to conceptualise solidarity as a common good: taking care of those in need, helping the local community, giving and receiving managerial support, mutual aid among workers, solidarity with customers, and solidarity beyond customers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This helps conceive solidarity as a common good as we seek the well-being according to the needs of others. For this reason, Frémeaux et al (2023) present six subgroups to conceptualise solidarity as a common good: taking care of those in need, helping the local community, giving and receiving managerial support, mutual aid among workers, solidarity with customers, and solidarity beyond customers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Aladwani [18], Frémeaux et al [19], and Molinillo [20] found that the quality of social support significantly influences stakeholder involvement in social commerce websites.…”
Section: The Essence Of Development Planningmentioning
confidence: 99%